2020
DOI: 10.1186/s12870-020-02697-6
|View full text |Cite
|
Sign up to set email alerts
|

BrrICE1.1 is associated with putrescine synthesis through regulation of the arginine decarboxylase gene in freezing tolerance of turnip (Brassica rapa var. rapa)

Abstract: Background In the agricultural areas of Qinghai-Tibet Plateau, temperature varies widely from day to night during the growing season, which makes the extreme temperature become one of the limiting factors of crop yield. Turnip (Brassica rapa var. rapa) is a traditional crop of Tibet grown in the Tibet Plateau, but its molecular and metabolic mechanisms of freezing tolerance are unclear. Results Here, based on the changes in transcrip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In the current study, our data demonstrated that pumpkin rootstock grafting played a positive role in putrescine synthesis and accumulation under chilling stress (Figure 2A), consistent with the up-regulated expression of the ADC gene (Figures 4, 7). Similarly, an increase in expression of the ADC gene and accumulation of putrescine under chilling stress have been reported in Brassica rapa (Yin et al, 2020). Moreover, a foliar spray D-arginine experiment further confirmed that putrescine under chilling stress in Cl/Cm inhibits ADC activity to modulate the metabolism of plants and the production of metabolites involved in stress tolerance (Song et al, 2014a(Song et al, , 2021Wu et al, 2016;Wang et al, 2019).…”
Section: Putrescine Synthesis Participates In Chilling Tolerance Indu...supporting
confidence: 59%
“…In the current study, our data demonstrated that pumpkin rootstock grafting played a positive role in putrescine synthesis and accumulation under chilling stress (Figure 2A), consistent with the up-regulated expression of the ADC gene (Figures 4, 7). Similarly, an increase in expression of the ADC gene and accumulation of putrescine under chilling stress have been reported in Brassica rapa (Yin et al, 2020). Moreover, a foliar spray D-arginine experiment further confirmed that putrescine under chilling stress in Cl/Cm inhibits ADC activity to modulate the metabolism of plants and the production of metabolites involved in stress tolerance (Song et al, 2014a(Song et al, , 2021Wu et al, 2016;Wang et al, 2019).…”
Section: Putrescine Synthesis Participates In Chilling Tolerance Indu...supporting
confidence: 59%
“…Second, from the view of biological characteristics, Taxus prefers a shady and humid environment (Wu & Wen, 2017 ). However, with the rising temperature, the climatic conditions such as strong radiation, drought, wind, and other adverse climatic conditions will be more severe in high‐altitude areas (Ouyang et al, 2022 ; Solomon et al, 2007 ; Yin et al, 2020 ). Thus, these adverse conditions will pose relatively more physiological constraints on T. chinensis , thus resulting in range reduction.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was observed between agmatine content and primary root growth rate, whereas no correlation was found with Put, or they were even negatively correlated. In this regard, the expression of BrrADC2.2 followed a cumulative pattern in accordance with Put levels in Tibetan turnip ( Brassica rapa ) under freezing conditions [ 162 ]. It was found that BrrICE1.1 (Inducer of CBF Expression 1) could directly interact with the BrrADC2.2 promoter, activating BrrADC2.2 to stimulate the accumulation of Put levels.…”
Section: Tolerance Responses To Abiotic Stressesmentioning
confidence: 99%